2019
DOI: 10.1186/s43055-019-0089-5
|View full text |Cite
|
Sign up to set email alerts
|

MDCT angiographic findings of various congenital pulmonary artery anomalies in pediatric patients

Abstract: Background: Congenital pulmonary artery anomalies are variable and need proper diagnosis and treatment. CT angiography with multiplanar reconstruction has the main role in the assessment of these anomalies and this noninvasive method should be the method of choice for preoperative planning and postoperative follow up. The aim of the study is to assess the value of MDCT in the detection of pulmonary arteries anomalies in the pediatric population with complex congenital heart disease in conjunction with echocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
4
2
0
Order By: Relevance
“…Our results were in agreement with two other studies, Harraz et al [16] and Soleimantabar et al [17]. Harraz et al [16], reported that MDCT was accurate in revealing pulmonary artery anomalies with 96% sensitivity, 100% specificity, 98% accuracy, 100% positive predictive value.…”
Section: Resultssupporting
confidence: 93%
“…Our results were in agreement with two other studies, Harraz et al [16] and Soleimantabar et al [17]. Harraz et al [16], reported that MDCT was accurate in revealing pulmonary artery anomalies with 96% sensitivity, 100% specificity, 98% accuracy, 100% positive predictive value.…”
Section: Resultssupporting
confidence: 93%
“…In this study, we detected 4 cases of truncus arteriosus type I according to van Praagh classification. This came in agreement with Harraz et al, 2019 [12], who reported also only 2 cases of type I.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, MSCT declared that the most common anomaly of the MPA was the MPA atresia which diagnosed in (26 cases, 34.2%), this came in agreement with Harraz et al, 2019 [12] who studied congenital pulmonary artery anomalies in pediatrics and reported also that the most common MPA anomaly was the MPA pulmonary atresia.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations